Ecthyma gangrenosum in a patient with non-Hodgkin lymphoma - Čolović Nataša; Grubor Nikica; Tanasilović Srđan; Čolović Radoje (Vojnosanitetski Pregled)
Introduction. Ecthyma gangrenosum is a rare disease of the skin that causes the localized necrosis of the skin and subcutaneous fat tissue, leading to the multiple ulcerations surrounded by local hyperaemia. The ulcerations are usually localized in groins, and perianal area. In the majority of cases ecthyma is caused by a Pseudomonas aeruginosa sepsis. The disease usually appears in immunocompromized, most frequently hematological patients. Case report. We presented a 78-year-old woman who had been treated for non-Hodgkin lymphoma for the last 18 years. She had recently been given cytotoxics which led to neutropenia. The patient suddenly developed high fever, chill and diarrhea, followed by ecthyma gangrenosum cutaneous lesions in groins, axillas, right side of the neck and umbilicus. Pseudomonas aeruginosa and Proteus mirabilis, that were sensitive to several antibiotics were isolated. The treatment included rehydratation, antibiotics, surgical debridement and regular dressing with antiseptics. The healing of all lesions was achieved after sixteen weeks of the treatment. Conclusion. If haemorrhagic- necrotic lesions of the skin are developed in immunocompromised, usually haematologic patients, an Ecthyma gangrenosum has to be considered immediately, material for identification of a cause has to be taken, followed by immediate administration of antibiotics effective against Pseudomonas aeruginosa. Surgical debridement and other therapeutic modalities are to be considered in some patients. .